If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 = -18 + 9c Solving 27 = -18 + 9c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-9c' to each side of the equation. 27 + -9c = -18 + 9c + -9c Combine like terms: 9c + -9c = 0 27 + -9c = -18 + 0 27 + -9c = -18 Add '-27' to each side of the equation. 27 + -27 + -9c = -18 + -27 Combine like terms: 27 + -27 = 0 0 + -9c = -18 + -27 -9c = -18 + -27 Combine like terms: -18 + -27 = -45 -9c = -45 Divide each side by '-9'. c = 5 Simplifying c = 5
| 7x+2=5x-6+8 | | 3(19x+20)=9(7+6x)-1 | | 17x-5=7+15x | | .6w-.4w+.3w=5 | | [k-10]=3 | | 5x+20=6x+8 | | 6(2x-9)+1=6(3x-7)-8(x+2) | | 20=4x+2 | | 2x+3=3x-15 | | 2x+5(2x+1)=7(x-1)-3 | | 2n-10n=40 | | 11x-8-6x=6x-7 | | 1.5x-5=x-4.5 | | 3(7x-8)=4(6x-3) | | 6x+5=-7+2x+20 | | 27=3c+-18+6c | | 7x+20=3x+30 | | 6x+4+15=36 | | 4(6-5x)=3(7-5x) | | [6m]=42 | | 3x+2(x+3)=4(2x-1)-5 | | 6-6x-4=-46+3x-15 | | 4(5x-6)=10x+12x-2x | | 8x+5=4(3x-2)-3 | | 21+1.5h=28-2h | | x^2-3xy+2y^2-y+x=0 | | 11-(2x+5)=-5x+7 | | x/3-1/2=1/2 | | 3+2(5x-4)=3(2x-3)+2x | | 13k+5=k-11 | | (33x)+(145y)=44000 | | (145x)+(33y)=44000 |